Efektivitas Edukasi Kesehatan Terhadap Kesiapan Menghadapi Menopause Pada Ibu Premenopause Di Wilayah Kerja PUSKESMAS Sonder - Sri Atikah; Meinita Wulansari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Menopause causes significant psychological symptoms in women due to the occurrence of physical and physiological changes as a result of decreased and ceased estrogen hormone production. The preliminary study results in the Sonder Primary Health Care Center area show that a significant portion of premenopausal mothers aged 45-50 years do not comprehend and lack understanding on how to cope with menopause. Additionally, there are concerns among these mothers regarding sexual issues after entering menopause.To determine the effectiveness of health education in preparing premenopausal mothers to face menopause in the working area of Puskesmas Sonder.This study employed a pre-experimental design with a one-group pretest-posttest design. The population consisted of 15 premenopausal women in the working area of Puskesmas Sonder, selected using simple random sampling. Data analysis involved univariate and bivariate analysis using Wilcoxon.Before health education, the majority of premenopausal mothers were categorized as unprepared to face menopause (53.3%). After receiving health education, a significant number of respondents were categorized as prepared to face menopause (80.0%). The effectiveness of health education in preparing premenopausal mothers to face menopause in the working area of Puskesmas Sonder was statistically significant (0.025 < 0.05).